A combined ex vivo and in vivo RNAi screen for notch regulators in drosophila reveals an extensive notch interaction network - Saj, Abil; Arzıman Büyükboduk, Zeynep; Stempfle, Denise; Belle, Werner van; Sauder, Ursula; Horn, Thomas; Dürrenberger, Markus; Paro, Renato; Boutros, Michael; Merdes, Gunter (Developmental cell, 2010)
Notch signaling plays a fundamental role in cellular differentiation and has been linked to human diseases, including cancer. We report the use of comprehensive RNAi analyses to dissect Notch regulation and its connections to cellular pathways. A cell-based RNAi screen identified 900 candidate Notch regulators on a genome-wide scale. The subsequent use of a library of transgenic Drosophila expressing RNAi constructs enabled large-scale in vivo validation and confirmed 333 of 501 tested genes as Notch regulators. Mapping the phenotypic attributes of our data on an interaction network identified another 68 relevant genes and revealed several modules of unexpected Notch regulatory activity. In particular, we note an intriguing relationship to pyruvate metabolism, which may be relevant to cancer. Our study reveals a hitherto unappreciated diversity of tissue-specific modulators impinging on Notch and opens new avenues for studying Notch regulation and function in development and disease.